2018
DOI: 10.1186/s12931-018-0892-y
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor gene polymorphisms and sex modify the association between acetaminophen use and asthma among young adults: results from two observational studies

Abstract: BackgroundEpidemiologic studies have demonstrated associations between acetaminophen use and asthma. This investigation sought to determine whether sex modifies the acetaminophen-asthma association and whether leptin (LEP) and leptin receptor (LEPR) gene polymorphisms modulate the sex-specific associations.MethodsData from the Isle of Wight birth cohort (IOW; n = 1456, aged 18 years) and Kuwait University Allergy (KUA; n = 1154, aged 18–26 years) studies were analyzed. Acetaminophen use and current asthma were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…However, recognizing that other human milk components and maternal factors could influence human milk composition, human milk leptin should be investigated in combination with milk concentrations of leptin-binding protein. 6,39 Although sex plays a role in the natural history of asthma development, 24 there is limited, if any, evidence that leptin in human milk is secreted in concentrations specific for infant sex and it remains unclear how sexspecific responses to nutritional stimuli could contribute to asthma and wheeze development. Furthermore, effect estimates in SPATZ were directionally opposite when using leptin measured at 6 weeks and 6 months of lactation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recognizing that other human milk components and maternal factors could influence human milk composition, human milk leptin should be investigated in combination with milk concentrations of leptin-binding protein. 6,39 Although sex plays a role in the natural history of asthma development, 24 there is limited, if any, evidence that leptin in human milk is secreted in concentrations specific for infant sex and it remains unclear how sexspecific responses to nutritional stimuli could contribute to asthma and wheeze development. Furthermore, effect estimates in SPATZ were directionally opposite when using leptin measured at 6 weeks and 6 months of lactation.…”
Section: Discussionmentioning
confidence: 99%
“…22,37,38 Additionally, leptin is apparently expressed differently between boys and girls, a phenomenon that may neither be solely explained by sex hormones nor the sex-dependent distribution of body fat. 13,14,39 Thus, physiologic sex-specific requirements of leptin may regulate human milk leptin concentrations. However, recognizing that other human milk components and maternal factors could influence human milk composition, human milk leptin should be investigated in combination with milk concentrations of leptin-binding protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study by Fuseini et al demonstrated the signal attenuation of house dust mite-induced type 2 and IL-17A inflammatory factors by the action of testosterone ( 41 ). Finally, the presence of sex-specific leptin and leptin receptor polymorphisms may also contribute to differences in asthma severity ( 42 ). Although the role of estrogen in allergic disease progression has been implicated, the results from such studies are inconclusive on whether the hormone leads to an ameliorative effect by inhibiting inflammasome activation or a pathologic effect by promoting type 2 proinflammatory cytokine production ( 43 , 44 ).…”
Section: Immunologic Basis Of Allergic Diseasesmentioning
confidence: 99%
“…Arginases, which are encoded by ARG1 and ARG2, are metabolized in vivo into L-arginine, which in turn generates nitric oxide (NO) in the presence of nitric oxide synthase (NOS), and NO is an endogenous bronchodilator. Ziyab et al found that ARG1 polymorphisms (rs2781659 and rs2781667) were related to acute SABAinduced bronchodilation in asthmatic patients (16). A Dutch asthma population-based cohort study demonstrated that 2 polymorphisms in ARG2 (rs17249437 and rs3742879) were related to asthma and more serious airway obstruction (17).…”
Section: β2-agonist-related Gene Variationsmentioning
confidence: 99%